Prevalence and factors associated with caesarean section among Tanzanian women of reproductive age: evidence from the 2022 Tanzania demographic and health survey data - Olorunfemi, Gbenga (BioMed Central, 2025)
Background: Caesarean Section (CS) is one of the commonest surgical procedures worldwide. It is an important medical intervention for reducing the risk of poor perinatal outcomes. However, there was increased trends in CS in sub-Saharan Africa as maternal and neonatal mortality and morbidity remains high. This study aims to determine the prevalence and factors associated with CS rates in Tanzania. Methodology: This was a secondary data analysis of 4,768 women of reproductive age (15–49) in Tanzania. The data utilized was from the Tanzania Demographic Health and Survey (TDHS) 2022. The factors associated with CS were identified using multivariable binary logistic regression. Results: Out of 4,768 women of reproductive age in Tanzania, 497 (10.4%) had CS. Attaining primary (Adjusted Odds Ratio (aOR): 1.79,95% CI 1.23–2.60), secondary (aOR:2.07,95% CI 1.36–3.14) and higher education (aOR: 2.35, 95% CI 1.08–5.12); having a husband/partner with higher education; being in richest household wealth quintile (aOR:1.98,95% CI (1.31-3.00), having a job (aOR:1.29, 95% CI: 1.05–1.58 and having attended more than 4 antenatal care (ANC) visits (aOR: 1.36, 95% CI: 1.11–1.67) were associated with a higher odds of undergoing CS compared to their respective counterparts. However, living in rural areas (aOR: 0.74, 95% CI:0.58–0.94), being multiparous women with 2–4 births (aOR: 0.67, 95% CI: 0.53–0.84) and 5 or more births (aOR: 0.44, 95% CI: 0.32–0.60) were associated with lower odds of CS. Conclusion: The overall prevalence of CS among women of reproductive age in Tanzania was 10.4%. The highest educational level, husband/partner’s educational attainment, household wealth quintile, type of residence, employment status, increased ANC number, and high parity were associated with CS. The CS prevalence is at the lower limit of the recommendation of the World Health Organisation of 10–15%. Further researches are necessary to highlight other barriers, facilitators and outcome of CSs in Tanzania to advise policy stakeholders.
Keywords: Caesarean Section; Women; Reproductive age; Tanzania; Health survey; SDG-3: Good health and well-being